Teología y belleza: en busca de la unidad perdida - Sánchez Cañizares, Javier (Veritas, 2011)
Modernity is epistemologically characterized by the division of knowledge. As a result, Protestant and Catholic Theology have both lacked a unifying vision in their reasoning about God. The acceptance of fragmentation in postmodern culture offers a new epistemological sensibility, which opens up inspiring possibilities for the rediscovery of transcendence. Among these possibilities, the intrinsically dialogical character of Creation aims at the via of beauty as a privileged path that Theology should explore in a descending and, especially, an ascending way.